2018
DOI: 10.1371/journal.pone.0202113
|View full text |Cite
|
Sign up to set email alerts
|

High TNFRSF12A level associated with MMP-9 overexpression is linked to poor prognosis in breast cancer: Gene set enrichment analysis and validation in large-scale cohorts

Abstract: BackgroundMatrix metalloproteinase-9 (MMP-9) is associated with remodelling of the extracellular matrix and invasion in various cancers. Identifying proteins connected to high MMP-9 expression is important in explaining its mechanisms. Our study aims to shed light on genes associated with high MMP-9 expression and discuss their clinical impact in breast cancer.MethodsWe evaluated 173 breast cancer cases from the Kangbuk Samsung Hospital, with 1964 cases from the Molecular Taxonomy of Breast Cancer Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…In accordance to Yang et al, 2018, this study revealed a significant relation between MMP9 expression and staging. However, there was no significant relation between MMP9 and grading in this study.…”
Section: Clinicopathologic Characteristicssupporting
confidence: 84%
“…In accordance to Yang et al, 2018, this study revealed a significant relation between MMP9 expression and staging. However, there was no significant relation between MMP9 and grading in this study.…”
Section: Clinicopathologic Characteristicssupporting
confidence: 84%
“…MMPs are secreted in the form of inactive proenzymes, whose activation is mediated via different molecular mechanisms ( 20 , 21 ). Thus, the level of active MMP9 in stromal cells and tumor cells may vary, which will subsequently account for the differences in clinical outcomes ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…High PRKD1 mRNA levels have been associated with low overall survival in TNBC (triple-negative breast cancer) [40]. TNFRS12A, also located in the 16p13.3 duplication, is responsible for poor prognosis in breast cancer, if overexpressed [41]. Although the results indicate some tumor-related methylation values of RAD9A, the relationship between tumor type, survival and RAD9A hypermethylation demands larger patients studies.…”
Section: Discussionmentioning
confidence: 95%